The KLF16/MYC feedback loop is a therapeutic target in bladder cancer - Lisi Zheng; Jingxuan Wang; Shan Han; Li Zhong; Zefu Liu; Bin Li; Ruhua Zhang; Liwen Zhou; Xianchong Zheng; Zhenhua Liu; Cuiling Zeng; Ruonan Li; et al. (Journal of Experimental & Clinical Cancer Research)
Abstract Background Bladder cancer (BLCA) is a common malignancy characterized by dysregulated transcription and a lack of effective therapeutic targets. In this study, we aimed to identify and evaluate novel targets with clinical potential essential for tumor growth in BLCA. Methods CRISPR-Cas9 screening was used to identify transcription factors essential for bladder cancer cell viability. The biological functions of KLF16 in bladder cancer were investigated both in vitro and in vivo. The regulatory mechanism between KLF16 and MYC was elucidated through a series of analyses, including RNA sequencing, quantitative polymerase chain reaction (qPCR), RNA immunoprecipitation, Western blotting, Mass spectrometry, Dual-luciferase reporter assays, Cleavage Under Targets and Tagmentation (CUT&Tag) sequencing, OptoDroplets assays, and RNA stability assay. The clinical relevance of KLF16 and MYC in bladder cancer was evaluated through analyses of public databases and immunohistochemistry. Results Krüppel-like factor 16 (KLF16) was essential for BLCA cell viability. Elevated expression of KLF16 was observed in bladder cancer tissues, and higher expression levels of KLF16 were correlated with poor progression-free survival (PFS) and cancer-specific survival (CSS) probabilities in BLCA patients. Mechanistically, KLF16 mRNA competed with the mRNA of dual-specificity phosphatase 16 (DUSP16) for binding to the RNA-binding protein, WW domain binding protein 11 (WBP11), resulting in destabilization of the DUSP16 mRNA. This, in turn, led to activation of ERK1/2, which stabilized the MYC protein. Furthermore, KLF16 interacted with MYC to form nuclear condensates, thereby enhancing MYC’s transcriptional activity. Additionally, MYC transcriptionally upregulated KLF16, creating a positive feedback loop between KLF16 and MYC that amplified their oncogenic functions. Targeting this loop with bromodomain inhibitors, such as OTX015 and ABBV-744, suppressed the transcription of both KLF16 and MYC, resulting in reduced BLCA cell viability and tumor growth, as well as increased sensitivity to chemotherapy. Conclusions Our study revealed the crucial role of the KLF16/MYC regulatory axis in modulating tumor growth and chemotherapy sensitivity in BLCA, suggesting that combining bromodomain inhibitors, such as OTX015 or ABBV-744, with DDP or gemcitabine could be a promising therapeutic intervention for BLCA patients.